2001
DOI: 10.1128/jb.183.20.5927-5936.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Adherence and Fibril Biogenesis by Actinobacillus actinomycetemcomitans : TadA Protein Is an ATPase

Abstract: Cells of Actinobacillus actinomycetemcomitans, a gram-negative pathogen responsible for an aggressive form of juvenile periodontitis, form tenaciously adherent biofilms on solid surfaces. The bacteria produce long fibrils of bundled pili, which are required for adherence. Mutations in flp-1, which encodes the major subunit of the pili, or any of seven downstream tad genes (tadABCDEFG) cause defects in fibril production, autoaggregation, and tenacious adherence. We proposed that the tad genes specify part of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 74 publications
(102 reference statements)
3
63
0
Order By: Relevance
“…O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation. Since then, similar findings have been reported for a number of bacteria and archaea, including (but not limited to) V. cholerae, A. actinomycetemcomitans, Aeromonas caviae, Shewanella oneidensis, Legionella pneumophila, Caulobacter crescentus, Deinococcus geothermalis, C. perfringens, and Sulfolobus acidocaldarius (40,44,102,133,178,342,389,398,408,431).…”
Section: Biofilm Formation and Remodelingsupporting
confidence: 49%
“…O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation. Since then, similar findings have been reported for a number of bacteria and archaea, including (but not limited to) V. cholerae, A. actinomycetemcomitans, Aeromonas caviae, Shewanella oneidensis, Legionella pneumophila, Caulobacter crescentus, Deinococcus geothermalis, C. perfringens, and Sulfolobus acidocaldarius (40,44,102,133,178,342,389,398,408,431).…”
Section: Biofilm Formation and Remodelingsupporting
confidence: 49%
“…Shown are the average twitching zone areas (12 zones each, four technical replicates from three independent plates) for unmodified and mutant proteins. and DotB of Legionella pneumophila (T4S) have been shown to be dominant-negative, whereas VirB11 (T4S) WA mutants have not (Bhattacharjee et al, 2001;Sakai et al, 2001;Stephens et al, 1995). Turner et al (1993) have shown that a WA mutant of XcpR (P. aeruginosa T2S ATPase) causes dominant-negative effects on secretion in the wild-type, but that the identical mutation in PilB does not affect the presence of external T4P in a wild-type strain, as assessed by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently proposed that tadA of A. actinomycetemcomitans is the first representative of a distinct subfamily of potential type IV secretion NTPase genes and that the flp-1-tadG gene cluster of this periodontal pathogen may encode a secretion system that is distinct from type II and type IV secretion systems (10). As it is found in both pathogenic and nonpathogenic species of bacteria, it is possible that this gene cluster encodes products that are not directly involved in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%